Land tenure security and forest cover in the Colombian Amazon - Jones, Kelly W.; Cabra-Ruiz, Nicolás; Correa Sánchez, Natalia; Molina González, Eduardo; Vélez, Maria Alejandra (Frontiers in Forests and Global Change, 2024)
Land tenure security (LTS) is important for achieving many sustainable development goals but its influence on forest cover is mixed. The uncertain relationship between LTS and forests is driven, in part, by the moderating influence of other drivers of deforestation. In this paper we illustrate this complex relationship between LTS and forest cover for individual private landholders in the Colombian Amazon. We use household surveys and econometric analysis with matching techniques to examine whether formal land titles and perceptions of LTS influence forest cover. We explore how the effect of a land title on forest cover is moderated by perceptions of LTS, time to markets, and participation in a conservation program. We find that more secure land tenure, on average, has a statistically significant and negative influence on forest cover in our sample. The negative association between LTS and forest cover is stronger when landholders perceive they have secure tenure and are closer to markets. However, we find the negative relationship between land title and forest cover goes away when a landholder participates in a conservation program. While our cross-sectional data and quasi-experimental methods cannot lead to causal statements, our results are in line with many recent studies in the Amazon region, and our household-level data provides important insight regarding drivers of deforestation that moderate the relationship between land title and forest cover. Our results inform the design of future LTS interventions and conservation efforts.